Design Criteria for Process-Based Restoration of Fluvial Systems. (30th June 2021) - Ciotti, Damion C; Mckee, Jared; Pope, Karen L; Kondolf, G Mathias; Pollock, Michael M
Abstract: Process-based restoration of fluvial systems removes human constraints on nature to promote ecological recovery. By freeing natural processes, a resilient ecosystem may be restored with minimal corrective intervention. However, there is a lack of meaningful design criteria to allow designers to evaluate whether a project is likely to achieve process-based restoration objectives. We describe four design criteria to evaluate a project's potential: the expansion of fluvial process space and connectivity lost because of human alterations, the use of intrinsic natural energy to do the work of restoration, the use of native materials that do not overstabilize project elements, and the explicit incorporation of time and adaptive management into project design to place sites on recovery trajectories as opposed to attempts to "restore" sites via a single intervention. Applications include stream and infrastructure design and low-carbon construction. An example is presented in California's Sierra Nevada foothills.